Organ-on-a-chip for studying immune cell adhesion to liver sinusoidal endothelial cells: the potential for testing immunotherapies and cell therapy trafficking - Kennedy, James I.; Davies, Scott P.; Hewett, Peter W.; Wilkinson, Alex L.; Oo, Ye H.; Lu, Wei-Yu; El Haj, Alicia J.; Shetty, Shishir (Frontiers in Cell and Developmental Biology, 2024)
Immunotherapy has changed the landscape of treatment options for patients with hepatocellular cancer. Checkpoint inhibitors are now standard of care for patients with advanced tumours, yet the majority remain resistant to this therapy and urgent approaches are needed to boost the efficacy of these agents. Targeting the liver endothelial cells, as the orchestrators of immune cell recruitment, within the tumour microenvironment of this highly vascular cancer could potentially boost immune cell infiltration. We demonstrate the successful culture of primary human liver endothelial cells in organ-on-a-chip technology followed by perfusion of peripheral blood mononuclear cells. We confirm, with confocal and multiphoton imaging, the capture and adhesion of immune cells in response to pro-inflammatory cytokines in this model. This multicellular platform sets the foundation for testing the efficacy of new therapies in promoting leukocyte infiltration across liver endothelium as well as a model for testing cell therapy, such as chimeric antigen receptor (CAR)-T cell, capture and migration across human liver endothelium.